Foreign Aid and the Status Quo: Evidence from Pre-Marshall Plan Aid. (2nd December 2019) - Markovits, Daniel; Strange, Austin; Tingley, Dustin
Abstract: Foreign aid has served as an important policy tool for centuries, yet international relations research essentially treats it as a novel, post-World War II phenomenon. We argue that documenting aid-like activities in earlier historical periods helps shed new light on the systemic political dynamics of aid giving. We introduce a framework that links aid giving to the status quo in international politics and populate the framework with a diverse set of historical and contemporary cases, including Western and non-Western donors. Our analysis reveals striking similarities between the ways in which donor governments from diverse regions, historical periods, and international systems have utilised aid and other forms of concessional finance to pursue international political goals. Our findings suggest that by considering the pre-Marshall Plan roots of aid researchers can more effectively link foreign aid provision to rising power dynamics, international formal and informal hierarchies, and other research agendas in international relations. Our analysis also points to the need for greater attention to non-Western and pre-World War II evidence in understanding the link between aid and systems of international relations that have been less prevalent in the post-Marshall Plan era.